The temporal role in grammatical performance of foreign language learners of English - Shojamanesh, Vafa; Tan, Kim Hua; Khazriyati Salehuddin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study evaluates the effects of length of formal learning time on the grammatical performance of English morphosyntactic structures among Iranian foreign language learners. Among different factors affecting language learning, the length of formal language exposure or language input is introduced as an important factor in language learning process. Thus, length of receiving input exposure in the form of formal classroom instruction in the current study is carefully studied by categorizing the participants in four different groups. The participants represented different exposure time groups by having various formal instruction hours at school and/or language center. In order to investigate the role of formal learning time on the performance of the individual morphosyntactic structures, the participants were presented to a timed Grammaticality Judgment Task. The task tested eleven different morphosyntactic structures and contained 132 sentences. The participants were asked to judge the grammaticality of the sentences and do the necessary corrections if needed. Repeated Measures ANOVA and regression analyses were performed to analyse the data. Results revealed the contribution of time on the performance of the individual structures.